First Field Record of the Tropical Red-Banded Thrips Selenothrips rubrocinctus (Thripidae: Panchaetothripinae) in Europe - Andrea Taddei (MDPI AG, 2021)
Red-banded thrips Selenothrips rubrocinctus is a polyphagous pest widely distributed in tropical and subtropical regions. Various fruit trees such as cacao, cashew, mango, avocado, and guava in certain habitats are attacked. This is the first report of the spontaneous occurrence of outdoor populations of this species of thrips in Europe. This species has been found in northern Italy on Liquidambar styraciflua, Carpinus betulus, and other ornamental forest species in urban areas. Barcode sequences of the Italian specimens were obtained.